Recent development in electrochemical biosensors for cancer biomarkers detection - Hasan, M.R.; Ahommed, M.S.; Daizy, M.; Bacchu, M.S.; Ali, M.R.; Al-Mamun, M.R.; Saad Aly, M.Aly; Khan, M.Z.H.; Hossain, S.I. (Biosensors and bioelectronics. X, 2021)
Cancer is the most frequent life-threatening disease which has the highest mortality rate throughout the world. Diagnosis of cancer at the early stage can plays a critical role for its effective and successful treatment. Traditional diagnostic methods for cancer screening are costly, time-consuming, and not practical for repeated screenings. However, a biomarker-based cancer diagnosis is emerging as one of the most promising strategies for early diagnosis, monitoring disease progression, and subsequent cancer treatment. This review describes the recent advances and improvements in the electrochemical biosensors designed for detecting various cancer biomarkers using different signal transduction techniques and biological recognition strategies. •Electrochemical biosensor helps to early diagnosis of cancer biomarkers.•Different electrochemical transduction system strategies are well explained.•More than 75 recent research articles on biosensors for cancer biomarker detection have been reviewed.•The advantages and future perspectives of each biosensor are highlighted.